PENGARUH PENYULUHAN HIV AIDS TERHADAP PENGETAHUAN DAN SIKAP REMAJA DI SMP KRISTEN YATIBA TINOOR KOTA TOMOHON TAHUN 2024 - Viranti, Viranti; Ilyas, Muh.; Zamli, Zamli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: HIV or Human Immunodeficiency Virus is a virus that attacks the body's immune system. AIDS or Acquired Immune Deficiency Syndrome is a group of disease symptoms that arise due to a decrease in the body's immunity caused by HIV infection. Adolescents at this stage often behave in ways that tend to be risky, such as juvenile delinquency (drugs) and the emergence of sexual urges such as premarital sex. Nowadays, teenagers' knowledge about sexuality is still relatively low. However, sexual activity has increased among teenagers, which is the main gateway for infectious diseases, one of which is HIV or AIDS. Objective: to determine the influence of HIV AIDS education on the knowledge and attitudes of teenagers at Yatiba Tinoor Christian Middle School, Tomohon City in 2024. Method: The research is a pre-experimental research with a One Group Pretest Posttest Designs research design where in this research design there is a group that is given treatment ( treatment) and have been observed previously (Pretest). The population and sample in this research were class VII students at Yatiba Tinoor Christian Middle School, Tomohon City, namely 30 respondents. Data collection uses power points and videos to provide health education. The data that has been collected is then processed and analyzed univariately and bivariately, the bivariate test used is the Dependent T-Test (Paired T-Test) statistical test using a laptop with the Microsoft Excel program and the statistical program (SPSS). Research Results: There is an influence of counseling about HIV/AIDS on the knowledge of Yatiba Tinoor Christian Middle School students in Tomohon City by showing that the knowledge t value before being given HIV/AIDS counseling (Pretest) is 8.839 and after being given counseling (Posttest) is 5.504 with a significant value or p value -value = .000 which means < 0.05 And there is an influence of counseling about HIV/AIDS on the attitudes of Yatiba Tinoor Christian Middle School students in Tomohon City with the attitude t value before being given HIV/AIDS counseling (Pretest) is 8.949 and after being given counseling (Posttest) is 5.615 with a significant value or p-value = .001 which means <0.05.Keywords: Counseling, HIV/AIDS, Knowledge, Attitude